ChemInform Abstract: Cu‐Mediated Enamide Formation in the Total Synthesis of Complex Peptide Natural Products. Issue 20 (20th May 2014) - Kuranaga, Takefumi; Sesoko, Yusuke; Inoue, Masayuki
Abstract Review: 131 refs.